The peripheral nature of the Western Aukštaitian subdialect of Šiauliai - Brazaitienė, Laura (Baltistica, 2025)
This article, based on audio recordings of dialects from the early 2010s, presents Zinkevičius and Girdenis’s study on the classification of the western Aukštaitian subdialect of Šiauliai and the bordering western, eastern, and southern Aukštaitian subdialects. An analysis of the subdialectal features that distinguish and are characteristic of the dialects under consideration in the classification of Lithuanian dialects shows that small changes in the use of some distinctive features can most likely be explained by the interaction between dialects as well as between them and the Standard Lithuanian language. Other distinctive features in the audio recordings can be associated with the characteristics of a secondary dialect forming based on the traditional dialect and the local Polish language.
Keywords: Lithuanian; Western Aukštaitian subdialect of Šiauliai; classification of Lithuanian dialects; Middle Aukštaitian; dialectal features; peripheral subdialects